Reconstructing the Guidance and Counseling Program Evaluation Model Based on Empathic Communication - Eko Puji Antoro (Program Studi Bimbingan dan Konseling Islam, 2026)
Evaluation of guidance and counseling (GC) programs in schools tends to be administratively oriented without measuring the quality of empathic communication, which is a determinant factor of service success. This study aims to reconstruct a GC program evaluation model by integrating empathic communication as a core assessment component. A qualitative approach with conceptual-analytical library research method was employed, utilizing content analysis, thematic analysis, and conceptual synthesis of relevant literature published between 2021–2026. The findings identify three primary gaps instrumental, conceptual, and practical and produce the BK-KE Model (Empathic Communication-Based Guidance and Counseling Evaluation), which integrates empathic communication indicators into five evaluation dimensions: Context, Input, Process, Product, and Impact. This model theoretically offers a more humanistic, accountable, and relational evaluation framework, though empirical validation through further developmental research across various educational levels remains necessary to confirm its effectiveness.